From Kosovo to Kabul and beyond : human rights and international intervention - Chandler, David, 1962- (Pluto Press, 2005)
'That the human rights rationale for interventionism is a genuine menace to democracy is convincingly demonstrated in this fine book.' Edward S. Herman.